Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the exact value of [tex]\(\tan 15^\circ\)[/tex] without using a calculator, we can use the tangent subtraction formula:
[tex]\[ \tan(A - B) = \frac{\tan A - \tan B}{1 + \tan A \tan B} \][/tex]
We choose [tex]\(A = 45^\circ\)[/tex] and [tex]\(B = 30^\circ\)[/tex]. Thus,
[tex]\[ \tan(15^\circ) = \tan(45^\circ - 30^\circ) \][/tex]
We know the exact values for [tex]\(\tan 45^\circ\)[/tex] and [tex]\(\tan 30^\circ\)[/tex]:
[tex]\[ \tan 45^\circ = 1 \][/tex]
[tex]\[ \tan 30^\circ = \frac{1}{\sqrt{3}} \][/tex]
Now, apply these values to the formula:
[tex]\[ \tan(15^\circ) = \frac{\tan 45^\circ - \tan 30^\circ}{1 + \tan 45^\circ \tan 30^\circ} \][/tex]
[tex]\[ \tan(15^\circ) = \frac{1 - \frac{1}{\sqrt{3}}}{1 + 1 \cdot \frac{1}{\sqrt{3}}} \][/tex]
Next, let's simplify both the numerator and the denominator separately.
First, simplify the numerator:
[tex]\[ 1 - \frac{1}{\sqrt{3}} = \frac{\sqrt{3}}{\sqrt{3}} - \frac{1}{\sqrt{3}} = \frac{\sqrt{3} - 1}{\sqrt{3}} \][/tex]
Now, simplify the denominator:
[tex]\[ 1 + 1 \cdot \frac{1}{\sqrt{3}} = 1 + \frac{1}{\sqrt{3}} = \frac{\sqrt{3}}{\sqrt{3}} + \frac{1}{\sqrt{3}} = \frac{\sqrt{3} + 1}{\sqrt{3}} \][/tex]
Next, we combine these simplified forms into the original formula:
[tex]\[ \tan(15^\circ) = \frac{\frac{\sqrt{3} - 1}{\sqrt{3}}}{\frac{\sqrt{3} + 1}{\sqrt{3}}} \][/tex]
Since both the numerator and the denominator are fractions with a common denominator of [tex]\(\sqrt{3}\)[/tex], we can simplify this to:
[tex]\[ \tan(15^\circ) = \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \][/tex]
To rationalize the denominator, multiply both the numerator and the denominator by the conjugate of the denominator, [tex]\(\sqrt{3} - 1\)[/tex]:
[tex]\[ \tan(15^\circ) = \frac{(\sqrt{3} - 1)(\sqrt{3} - 1)}{(\sqrt{3} + 1)(\sqrt{3} - 1)} \][/tex]
[tex]\[ \tan(15^\circ) = \frac{(\sqrt{3} - 1)^2}{(\sqrt{3})^2 - (1)^2} \][/tex]
Now simplify the expression further:
[tex]\[ (\sqrt{3} - 1)^2 = (\sqrt{3})^2 - 2 \cdot \sqrt{3} \cdot 1 + 1^2 = 3 - 2\sqrt{3} + 1 = 4 - 2\sqrt{3} \][/tex]
[tex]\[ (\sqrt{3})^2 - (1)^2 = 3 - 1 = 2 \][/tex]
Thus:
[tex]\[ \tan(15^\circ) = \frac{4 - 2\sqrt{3}}{2} = \frac{4}{2} - \frac{2\sqrt{3}}{2} = 2 - \sqrt{3} \][/tex]
Finally, simplifying further:
[tex]\[ \tan(15^\circ) = \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \cdot \frac{\sqrt{3} - 1}{\sqrt{3} - 1} = 0.26794919243112264 \][/tex]
We find that the value of [tex]\(\tan 15^\circ\)[/tex] is approximately [tex]\(0.26794919243112264\)[/tex].
[tex]\[ \tan(A - B) = \frac{\tan A - \tan B}{1 + \tan A \tan B} \][/tex]
We choose [tex]\(A = 45^\circ\)[/tex] and [tex]\(B = 30^\circ\)[/tex]. Thus,
[tex]\[ \tan(15^\circ) = \tan(45^\circ - 30^\circ) \][/tex]
We know the exact values for [tex]\(\tan 45^\circ\)[/tex] and [tex]\(\tan 30^\circ\)[/tex]:
[tex]\[ \tan 45^\circ = 1 \][/tex]
[tex]\[ \tan 30^\circ = \frac{1}{\sqrt{3}} \][/tex]
Now, apply these values to the formula:
[tex]\[ \tan(15^\circ) = \frac{\tan 45^\circ - \tan 30^\circ}{1 + \tan 45^\circ \tan 30^\circ} \][/tex]
[tex]\[ \tan(15^\circ) = \frac{1 - \frac{1}{\sqrt{3}}}{1 + 1 \cdot \frac{1}{\sqrt{3}}} \][/tex]
Next, let's simplify both the numerator and the denominator separately.
First, simplify the numerator:
[tex]\[ 1 - \frac{1}{\sqrt{3}} = \frac{\sqrt{3}}{\sqrt{3}} - \frac{1}{\sqrt{3}} = \frac{\sqrt{3} - 1}{\sqrt{3}} \][/tex]
Now, simplify the denominator:
[tex]\[ 1 + 1 \cdot \frac{1}{\sqrt{3}} = 1 + \frac{1}{\sqrt{3}} = \frac{\sqrt{3}}{\sqrt{3}} + \frac{1}{\sqrt{3}} = \frac{\sqrt{3} + 1}{\sqrt{3}} \][/tex]
Next, we combine these simplified forms into the original formula:
[tex]\[ \tan(15^\circ) = \frac{\frac{\sqrt{3} - 1}{\sqrt{3}}}{\frac{\sqrt{3} + 1}{\sqrt{3}}} \][/tex]
Since both the numerator and the denominator are fractions with a common denominator of [tex]\(\sqrt{3}\)[/tex], we can simplify this to:
[tex]\[ \tan(15^\circ) = \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \][/tex]
To rationalize the denominator, multiply both the numerator and the denominator by the conjugate of the denominator, [tex]\(\sqrt{3} - 1\)[/tex]:
[tex]\[ \tan(15^\circ) = \frac{(\sqrt{3} - 1)(\sqrt{3} - 1)}{(\sqrt{3} + 1)(\sqrt{3} - 1)} \][/tex]
[tex]\[ \tan(15^\circ) = \frac{(\sqrt{3} - 1)^2}{(\sqrt{3})^2 - (1)^2} \][/tex]
Now simplify the expression further:
[tex]\[ (\sqrt{3} - 1)^2 = (\sqrt{3})^2 - 2 \cdot \sqrt{3} \cdot 1 + 1^2 = 3 - 2\sqrt{3} + 1 = 4 - 2\sqrt{3} \][/tex]
[tex]\[ (\sqrt{3})^2 - (1)^2 = 3 - 1 = 2 \][/tex]
Thus:
[tex]\[ \tan(15^\circ) = \frac{4 - 2\sqrt{3}}{2} = \frac{4}{2} - \frac{2\sqrt{3}}{2} = 2 - \sqrt{3} \][/tex]
Finally, simplifying further:
[tex]\[ \tan(15^\circ) = \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \cdot \frac{\sqrt{3} - 1}{\sqrt{3} - 1} = 0.26794919243112264 \][/tex]
We find that the value of [tex]\(\tan 15^\circ\)[/tex] is approximately [tex]\(0.26794919243112264\)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.